2020
DOI: 10.2147/ndt.s258475
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Characteristics of Pesticide Self-Harm as Associated with Suicide Attempt Repetition Status</p>

Abstract: Purpose: Previous suicide behavior predicts future suicide risk. Studies of suicide repetition are important for suicide prevention. This study examined the clinical characteristics and psychiatric comorbidities of pesticide self-harm as associated with suicide attempt repetition status. Patients and Methods: This retrospective, observational study included patients admitted to a medical center in northern Taiwan between 2000 and 2015 following suicide attempts by pesticide. Diagnoses were made by a consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…higher dose of alcohol consumed led to higher amount of OP ingested and increased the likelihood of death Gawarammana et al (Sri Lanka) [ 63 ] Clinical effects and toxicokinetics of bispyribac self-poisoning Cohort Two general hospitals 110 patients with bispyribac poisoning Acute 14.5% of patients had co-ingested alcohol. Of the three patients who died, two had co-ingested alcohol Huang et al (Taiwan) [ 64 ] Clinical and psychiatric characteristics of self-harm with OP, carbamates, or glyphosates Cohort One hospital 151 self-poisoning cases who received a psychiatric evaluation Acute and chronic Alcohol intoxication assessed for complex suicides (> 1 method) of which 54.2% were recorded as alcohol intoxicated, this was similar for repeated (55%) and non-repeated self-harm (53%). Among all patients who were assessed, 25.8% had alcohol use disorder, which was higher among repeaters (34.9%) than non-repeaters (22.2%) (NS) Kim and Lee (Republic of Korea) [ 65 ] Co-ingestion of alcohol in self-poisoning (any poison) Cohort One general hospital 286 deliberate self-poison patients Acute 64% of the sample had co-ingested alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…higher dose of alcohol consumed led to higher amount of OP ingested and increased the likelihood of death Gawarammana et al (Sri Lanka) [ 63 ] Clinical effects and toxicokinetics of bispyribac self-poisoning Cohort Two general hospitals 110 patients with bispyribac poisoning Acute 14.5% of patients had co-ingested alcohol. Of the three patients who died, two had co-ingested alcohol Huang et al (Taiwan) [ 64 ] Clinical and psychiatric characteristics of self-harm with OP, carbamates, or glyphosates Cohort One hospital 151 self-poisoning cases who received a psychiatric evaluation Acute and chronic Alcohol intoxication assessed for complex suicides (> 1 method) of which 54.2% were recorded as alcohol intoxicated, this was similar for repeated (55%) and non-repeated self-harm (53%). Among all patients who were assessed, 25.8% had alcohol use disorder, which was higher among repeaters (34.9%) than non-repeaters (22.2%) (NS) Kim and Lee (Republic of Korea) [ 65 ] Co-ingestion of alcohol in self-poisoning (any poison) Cohort One general hospital 286 deliberate self-poison patients Acute 64% of the sample had co-ingested alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…One study of patients presenting to a medical centre in Taiwan only included complex suicide cases (i.e. cases with at least one other means in addition to pesticides), of whom more than half (54%) had ‘alcohol intoxication’ (assessment method not reported) with no significant difference between those with and without previous events of self-harm (‘suicide attempts’) [ 64 ]. A Sri Lankan study across three hospitals was the only study that assessed BAC and found that more than half of patients (51%) had a BAC ≥ 0.05 mg/dL and a median of 0.15 mg/dL [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticide self-poisoning is a widely used means of suicide, and one of the most popular approaches of suicide worldwide. 37 It comprises an important public health issue in Asian nations. 38 Suicide by intentional ingestion of pesticides is common in Taiwan because of easy access.…”
Section: Discussionmentioning
confidence: 99%